Equilibrium real exchange rate estimates across time and space - Christoph Fischer (Deutsche Bundesbank, 2019)
Equilibrium real exchange rate and corresponding misalignment estimates differ tremendously depending on the panel estimation method used to derive them. Essentially, these methods differ in their treatment of the time-series (time) and the cross-section (space) variation in the panel. The study shows that conventional panel estimation methods (pooled OLS, fixed, random, and between effects) can be interpreted as restricted versions of a correlated random effects (CRE) model. It formally derives the distortion that arises if these restrictions are violated and uses two empirical applications from the literature to show that the distortion is generally very large. This suggests the use of the CRE model for the panel estimation of equilibrium real exchange rates and misalignments.
Keywords: F31; C23; 330; equilibrium real exchange rate; panel estimation method; correlated random effects model; productivity approach; BEER; price competitiveness